Current and Common Definitions of Treatment-Resistant Depression: Findings from a Systematic Review and Qualitative Interviews. (June 2019) - Brown, Sage; Rittenbach, Katherine; Cheung, Sarah; McKean, Gail; MacMaster, Frank P.; Clement, Fiona
Objective: No universal definition for treatment-resistant depression (TRD) exists. This lack of consensus reduces the generalizability of study findings and limits the ability to study TRD. In addition, anecdotally, there may be a difference between the definitions of TRD within research and those applied in practice. Thus, the objective of this work was to identify current common definitions of TRD used in both research and clinical practice. Method: A systematic review of published literature was conducted to document TRD definitions. Extracted data were grouped based on patient cohort and method of defining TRD. Validation studies were narratively summarized. Interviews with 6 key informants were conducted to understand how definitions are applied in practice. Results: In total, 155 definitions for TRD were identified in the published literature, and 48.4% of all definitions specified requirement of at least 2 treatment failures. Key informant interviews indicated the concept of TRD is rarely employed in clinical practice. Instead, concepts like "complex needs, " "struggling with their disease, " and "chronic" are used. When asked directly about how they would define TRD, interview participants said an adequate trial of psychotherapy as well as an adequate trial of at least 2 to 3 antidepressant medications. Conclusions: There is no universally accepted definition of TRD, and substantial heterogeneity exists. This study indicates discordance between the use of the term in research and clinical practice, with several key informants emphasizing that the terminology is rarely used in their clinical experience. Development of a shared, common definition across practice and research is required.